The Effect Of Providing Verbal Reinforcement On Students' Learning Behavior In Class V At Sdn Brangkal 2, Bandar Kedungmulyo, Jombang - Ega Aimmatuzzakia; Emy Yunita Rahma Pratiwi (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2022)
This research was conducted by providing verbal reinforcement to the fifth grade students by giving a questionnaire sheet to find out the results of the learning carried out by the teacher. Lack of verbal reinforcement of learning behavior makes students have a negative nature. In this case the provision of verbal reinforcement has a positive impact on learning behavior which will increase student learning outcomes and teachers get learning objectives well. This study uses a quantitative approach with ex post facto research methods. The subjects in this study were students of class V SDN Brangkal 2, totaling 10 children. Data collection techniques using observation, questionnaires, and documentation. The data analysis used is to calculate the results of the questionnaire on verbal reinforcement and learning behavior followed by calculating the correlation coefficient. The research was conducted in the even semester of the 2020/2021 academic year. The research was conducted by giving a questionnaire sheet. The first is verbal reinforcement and the second is student learning behavior. The results of the research conducted at SDN Brangkal 2 showed that the results of the verbal reinforcement questionnaire were 59.2 and the results of the student learning behavior questionnaire were 59.7 of these results followed by the correlation test with the results of 0.94 which indicated that there was an effect of giving verbal reinforcement on behavior Student learning behavior is seen from the correlation coefficient interpretation guidelines. Thus Ho is rejected and Ha is accepted so that it is concluded that there is an effect of providing verbal reinforcement on the learning behavior of fifth grade students at SDN Brangkal 2, Bandar Kedungmulyo District, Jombang Regency. Keywords: Giving Verbal Reinforcement, Learning Behavior